Delignification and Adsorption Research of Bioethanol Process using Pseudostem of Musa Balbisiana (Pisang Klutuk) as the Blending Raw Material to Gasohol - Rafit Arjeni; Abu Hasan; Aida Syarif (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2023)
Indonesia is a country that has the most energy sources in the Southeast of Asia and the fifth in Asia-Pacific subsequent to China, India, Japan and South Korea. Energy usage in Indonesia in 2016 was still dominated by 47% fuel oil. If the energy usage increases continuously, energy sustenance and resilience in Indonesia will be plagued. Therefore, there is a necessary to utilize the alternative energy sources that would be earth-friendly as well New and Renewable Energy (EBT) like bioethanol. Bioethanol can be produced by organic wastes, pseudostem of Musa Balbisiana (Pisang Klutuk) as the example. This research is focused on the study of delignification and adsorption of the process of bioethanol using pseudostem of Musa Balbisiana as the blending raw material to gasohol. The process started with the pre-treatment and delignification of the pseudostem of Musa Balbisiana with the sorts of NaOH concentration including the following of 10%, 20%, 30% and 100oC, 125oC, 150oC, 175oC, dan 200oC for the heating temperatures. In delignification, it can be stated that the concentration of 10% NaOH on 150oC temperature produced the finest cellulose and lignin content with the amount of 81,3% cellulose and 10,1% lignin. The pseudostem fibers that have passed the process of delignification, was done to the process of hydrolysis and fermentation for producing bioethanol. The result of Bioethanol was carried out to the process of distillation for separating bioethanol and water. Continuing the process, bioethanol was purified in adsorption and distillation process. In adsorption, the 5gr, 10gr, 15gr, 20gr, and 25gr adsorbent alloyed to the purified bioethanol, and it can be claimed that the highest rate of purified bioethanol is 20gr with the 99,11% bioethanol content. The 99,11% bioethanol content was blending with Pertalite with the ratios of 5:95, 10:90, 15:85, 20:80, and 25:75, thereafter it was analyzed the RON content which obtained the highest point that is 97,48 on 25:75 ratio.